New activators for the completion of phagocytosis to prevent the reactivation of the tuberculosis process - Martynov, Artur; Romanova, Olena; Pohorila, Marina; Sydorenko, Tetyana; Igumnova, Natalia; Yukhimenko, Vera; Shcherbak, Olena (Annals of Mechnikov's Institute, 2021)
In order to develop dosage forms for the prevention of reactivation of latent tuberculosis, several pharmaceutical compositions were synthesized, from which the most effective activator of phagocytosis completion - succinylformyllysine - was selected. It was found that the use of succinylformillisin increases the functional activity of T-lymphocytes and peritoneal macrophages, normalizes the leukogram of the blood. The most effective composition of diprion and cholecalciferol, capable of inhibiting mycobacterial urease and selective activation of the functional ability of phagocytes and lymphocytes, has also been developed. The aerosol mixture based on these compounds is able to reduce by 37% the number of macrophages with incomplete phagocytosis in the lungs of mice infected with BCG on the background of immunosuppression. DOI: 10.5281/zenodo.5499622